ORIENTASI NILAI BUDAYA PETANI RUMPUT LAUT DALAM PEMBANGUNAN DI DESA PED KECAMATAN NUSA PENIDA - Ni Made Suwendri (Universitas Warmadewa, 2018)
[Title: Cultural Value Orientation of the Seaweed Planters in Developing Ped Village, Nusa Penida District] Human’s cultural value orientation becomes important factor in achieving the purpose. It can be seen from its view ofliving.This research is purposed to get the deep understanding of cultural value orientation seaweed plantersin building of Ped Village, Nusa Penida District. This research used qualitative approach which is supported byquantitative data. The technique of collecting data is done through observation' concern interview, and library research. The data is analyzed throughqualitative descriptive way. According to the empiric data, it shows that the cultural value orientation whichis used by seaweed planters in Ped village, Nusa Penida district in solving theliving problems including of their views to the principal of life, principal of work, principalof time, principal of human, and principal of human's relation with nature. Mostof the principal goes to the improvement. The orientation shows theimportant dynamic for the successful of building in Nusa Penida District.